Trends and challenges for microporous polymers. (19th April 2017) - Chaoui, Nicolas; Trunk, Matthias; Dawson, Robert; Schmidt, Johannes; Thomas, Arne
Abstract : Recent trends and challenges for the emerging materials class of microporous polymers are reviewed. See the main article for graphical abstract image credits. Abstract : Microporous polymers are covalently bound, entirely organic materials which possess very high surface areas. These materials have been intensively studied within recent years and various interesting properties and possible applications have been discovered and described. This review article starts with the question, what makes microporous polymers special and are there certain features which differentiate them from other microporous materials? Indeed, there are some special structural and functional features found in microporous polymers which make them really unique and merit further exploration. We focus here on microporous polymers which are solution-processable, can be produced as thin films on electrodes by oxidative polymerizations, are π-conjugated organic semiconductors, or which provide the possibility to introduce and exploit distinct functional groups in an otherwise non-functional highly porous environment. Emerging applications for these microporous polymers which make explicit use of these unique features are further presented.